Angry young men how parents, teachers, and counselors can help "bad boys" become good men - Kipnis, Aaron R. (San Francisco, Calif. Jossey-Bass, 1999)
Writing from personal and professional experience, Aaron Kipnis shares both the riveting story of his own troubled youth-and how he turned himself around-and the successful approaches he has used to help "bad boys" become good men. Angry Young Men offers specific, practical advice for parents, teachers, counselors, community leaders, and justice professionals-- everyone who wants to help at-risk boys become strong, productive, caring, and compassionate men. "Angry Young Men is an extremely important book that is especially timely now during our current epidemic of violence by and against boys and young men ... Aaron Kipnis has seen deeply, not only into the souls of troubled boys and adolescents, but also into those aspects of the spirit of our culture and our epoch that have turned an unprecedentedly large portion of our boys and young men into the perpetrators and victims of violence."--The Foreword by James Gilligan, M.D., Department of Psychiatry, Harvard Medical School Annotation. Kipnis, a popular national speaker and consultant on male psychology, draws on his own experiences as a youth living in foster homes, juvenile institutions, and on the streets as he examines the lives of boys at risk and offers practical suggestions for helping troubled boys become good men. He tells parents what they need to know if a son is having trouble emotionally or socially, or with drugs or gangs, and offers counselors and educators insight on working with disruptive boys.
Bad boys -- Living in a house on fire -- Slipping through the cracks at school -- Mean streets -- Juvenile injustice -- Drugs and criminalization -- Youth corrections and gangs -- The American gulag -- From bad boys to good men -- Honoring the spirit of young men.
Includes bibliographical references and index.
Keywords: Male juvenile delinquents -- United States; Juvenile delinquency -- United States -- Prevention